Coffee Lappara product branding training at the Perpustakaan Kambing Community - Arni Arni; Syukri Syukri; Sitti Rahmawati Arfah; Nasta Inul Haq (Community Empowerment, 2022)
The Perpustakaan Kambing Community is a group of people who are trying to assist coffee farmers with the farming knowledge and education. This community also maintains the Coffee Lappara brand, which transforms coffee beans into packaged black coffee products. Efforts to enhance the welfare of Lappara coffee producers, however, ran into obstacles as the project progressed. One of the challenges the Perpustakaan Kambing faces is a lack of product branding knowledge, which has resulted in their coffee business failing to grow at all. This service seeks to improve understanding of how to use the seven aspects of branding to lappara coffee products. The technique of implementation is interactive discussion, coaching, and assistance. In the end of the program, partners are able to determine the content of the seven basic parts of branding, including target market, target audience, and brand recruiters, brand name, brand slogan, brand style, and logo design, as a result of this activity.